Microorganisms inhabiting follicular contents of facial acne are not only Propionibacterium but also Malassezia spp - Akaza, Narifumi; Akamatsu, Hirohiko; Numata, Shigeki; Yamada, Shunji; Yagami, Akiko; Nakata, Satoru; Matsunaga, Kayoko (Journal of dermatology, 2016)
To clarify the relationship between major cutaneous microorganisms (Propionibacterium, Staphylococcus and Malassezia spp.) and acne vulgaris (acne), we examined the microbiota quantitatively in the follicular contents of inflammatory acne and on the facial skin of patients with acne. Fifteen Japanese untreated acne outpatients were studied. The follicular contents from inflammatory acne lesions of the face were collected using a comedo extractor. The skin surface samples were obtained by the swab method from 10 cm2 of facial skin. The microbiota was analyzed using polymerase chain reaction. The microbiota in follicular contents was similar to that on the skin surface, namely, there were large populations of Propionibacterium spp., Staphylococcus spp. and Malassezia spp. Moreover, the number of Malassezia spp. on the skin surface was correlated with that of inflammatory acne and that in follicular contents. This study clarified that there are large populations of Propionibacterium spp., Staphylococcus spp. and Malassezia spp. in follicular contents. These results suggest the possibility that not only Propionibacterium acnes but also other cutaneous resident microorganisms are related to acne. Particularly, we considered that Malassezia spp. is closely related.